First record of Beaded Lacewings (Neuroptera, Berothidae) from Colombia - Ardila-Camacho, Adrián (Zootaxa, 2013)
The family Berothidae is recorded for the first time in Colombia, with Spiroberotha sanctarosae Adams, 1989, collect-ed from Tayrona National Park and Zambrano municipality, in Magdalena and Bolívar departments, respectively. The external morphology and male genitalia are illustrated, providing complementary information to the original descrip-tion. A key to separate species of Spiroberotha, as well as a list of species of Central- and South American Berothidae are presented.